Sjeldne fugler i Norge i 2002 - Rapport fra Norsk sjeldenhetskomité for fugl (NSKF) - Bunes, Vegard; Solbakken, Kjetil Aadne (Ornis Norvegica, 2004)
This is the 27th annual report and the 28th announcement from the Norwegian Rarities Committee (NSKF). Most of the records treated here are from 2002, but older records are also included. The systematic list of accepted records is set out in the following system: (1) The birds Norwegian name, (2) scientific name, (3) the numbers in brackets, e.g. (30/32 - 1), refers respectively to the total number of records/total number of individuals up to and including 2001, and in 2002, (4) any limitations given of (3), (5) any breeding, (6) year, (7) county, (8) number of individuals, age (1K = first calendar year etc.), sex (if known) and sometimes circumstances («ringmerket» means that the bird was ringed), (9) site and municipality, (10) date, (11) * indicates if the record was complemented by positive evidence, and type of the evidence (F = photo, V = video-recorded, L = tape-recorded, D = found dead), (12) observers names in brackets, main observer is specified first and emphasized with *, (13) roughly gives the species distribution and (14) comments concerning the records. General trends: Norway experienced a major influx of Rose-coloured Starlings Sturnus roseus in the summer and autumn of 2002. This influx included 26 records, which increased the total number of accepted records with 20 %. The year 2002 was also the first year with more than one accepted Balearic Shearwater Puffinus mauretanicus (three records). Five records of Bittern Botaurus stellaris and eight records of Little Egret Egretta garzetta were also year records. The number of accepted Water Pipits Anthus spinoletta was doubled with three new records. It was also a record year for Blyth’s Pipit Anthus godlewskii (two records), Pechora Pipit Anthus gustavi (three records) and Citrine Wagtail Motacilla citreola (six records). Eight records of Great White Egret Ardea alba was a second best year ever. Other records of interest included a drake Blue-winged Teal Anas discors (5th record), three Spectacled Eiders Somateria fischeri (4th record), Harlequin Duck Histronicus histronicus (7th record), Short-toed Eagle Circaetus gallicus (3rd record), Black-winged Pratincole Glareola nordmanni (3rd record), Greater Sand Plover Charadrius leschenaultii (3rd record), Semipalmated Sandpiper Calidris pusilla (4th record), Upland Sandpiper Bartramia longicauda (2nd record), Spotted Sandpiper Actitis macularia (5th record), Scops Owl Otus scops (2nd record), Lanceolated Warbler Locustella lanceolata (6th record) and Pallas’s Grasshopper Warbler Locustella certhiola (7th record). Species and subspecies new to the Norwegian list: This report includes five additions to category A on the Norwegian list: Lesser Sand Plover Charadrius mongolus, American Golden Plover Pluvialis dominica, Eastern Crowned Warbler Phylloscopus coronatus, Eastern Bonelli’s Warbler Phylloscopus orientalis and White-throated Sparrow Zonotrichia albicollis. A record of Egyptian Goose Alopochen aegyptiacus was also added to the Norwegian category C list. With these new records the official Norwegian birdlist consists of 464 species. A record of Ross’s Goose Chen rossii migrating south with Barnacle Geese Branta leucopsis was probably the same individual as recorded in Northumberland,Great Britain a few days later, and is accepted as a new species in the Norwegian category D. The first breeding attempt of Pied-billed Grebe Podilymbus podiceps was also recorded in 2002, resulting in a hybrid chick with genes from Little Grebe Tachybabtus ruficollis.